'Postnatal growth during the first five years of life in SGA and AGA neonates with reduced fetal growth'. (December 2020) - Hendrix, M.L.E.; van Kuijk, S.M.J.; El Bahaey, S.E.; Gerver, W.J.M.; Feron, F.J.M.; Kuin, M.E.; Spaanderman, M.E.A.; Bons, J.A.P.; Al-Nasiry, S.
Abstract: Background: Even though a lot of research has been done on postnatal growth and the occurrence of catch-up growth in small-for-gestational age (SGA) neonates, this phenomenon has not been studied well in appropriate-for-gestational age (AGA) neonates. Postnatal catch-up growth may also occur in AGA neonates indicating a compensatory mechanism for undiagnosed intrauterine growth restriction, especially in AGA neonates with reduced fetal growth velocity. Aims: To describe postnatal growth during the first 5 years of life in SGA and AGA neonates and evaluating the role of fetal growth velocity in catch-up growth. Study design: Retrospective study in a Dutch tertiary hospital. Subjects: 740 singleton neonates, without congenital anomalies, with ultrasound fetal growth data from 20 weeks and 32 weeks of pregnancy. Outcome measures: Postnatal growth measurements of height (cm) and weight (kg) from birth until five years of age. Postnatal catch-up growth defined as difference (delta) in both height and weight between 4 weeks and 3 years of age. Results and conclusions: SGA neonates had a significantly lower height and weight compared to the AGA group for all available measurement moments till 3 years. The catch-up growth between the SGA and AGA groups from 4 weeks up to 3 years after birth was not different between the two groups. However, neonates with reduced fetal growth velocity had a significantly higher risk for catch–up growth in height during the first 3 years after birth. This suggests a role for fetal growth velocity measurement in predicting fetal and subsequent postnatal growth potential. Highlights: Neonates with a reduced fetal growth velocity show catch-up growth postnatally. Fetal growth velocity in addition to birthweight percentile can be linked to catch-up growth. There is a possible role for fetal growth velocity between second and third trimester in predicting postnatal growth pattern.